PROGRESS AND PROBLEMS IN THE ECONOMIC DEVELOPMENT OF LIBYA - Wedle, William (Dirasat in Economics and Business, 1968)
At the time of independence, the per capita income in Libya was estimated to be about £L 11 (30) per year.¹ At that time, the outlook for the future was bleak, and economic experts were urging Libya to attempt to capture a larger share of the foreign aid handouts of other countries. Two and a half decades later, the situation was very different. The successful exploration, production, and exportation of petroleum had vastly transformed the economy and provided a major impetus to growth. No longer was Libya dependent upon foreign aid.